How to reach trustworthy decisions for caesarean sections on maternal request: a call for beneficial power - Eide, T. (Journal of medical ethics, 2021)
Caesarean delivery is a common and life-saving intervention. However, it involves an overall increased risk for short-term and long-term complications for both mother and child compared with vaginal delivery. From a medical point of view, healthcare professionals should, therefore, not recommend caesarean sections without any anticipated medical benefit. Consequently, caesarean sections requested by women for maternal reasons can cause conflict between professional recommendations and maternal autonomy. How can we assure ethically justified decisions in the case of caesarean sections on maternal request in healthcare systems that also respect patients’ autonomy and aspire for shared decisions? In the maternal-professional relationship, which can be characterised in terms of reciprocal obligations and rights, women may not be entitled to demand a C-section. Nevertheless, women have a right to respect for their deliberative capacity in the decision-making process. How should we deal with a situation of non-agreement between a woman and healthcare professional when the woman requests a caesarean section in the absence of obvious medical indications? In this paper, we illustrate how the maternal-professional relationship is embedded in a nexus of power, trust and risk that reinforces a structural inferiority for women. To accommodate for beneficial use of power, these decision processes need to be trustworthy. We propose a framework, inspired by Lukes’ three-dimensional notion of power, which serves to facilitate trust and allows for beneficial power in shared processes of decision-making about the delivery mode for women requesting planned C-sections.There are no data in this work.